Cozy interiority - Jeppe Trolle Linnet (Ambiances)
The atmosphere of coziness, or “hygge” as it is referred to in Denmark, gives certain places such as cafés a particular appeal, that of providing an experience of pleasant relaxation in the here and now. This article argues that coziness can be seen as a pleasant experience of interiority, and that there are new and valuable understandings of such urban atmospheres to be gained by considering the role of co-presence with other people: How subjects relate both to fellow consumers on site, and the surrounding urban crowd. The article calls attention to the way that social and material dynamics interrelate in constituting this form of urban ambience, as the weaving of intersubjective space mirrors the interiority and porosity of material form. What arises is an experience of being pleasantly, anonymously co-present with other people’s social circles and urban movements.